Features of the reform of the judicial system in the context of the development of the public administration of Ukraine - Salnikov, Oleksiy (Public Administration and Regional Development, 2023)
The article deals with the principles of reforming public administration in Ukraine, starting from 1991 and covering the period of its independence, emphasizing the need to consider the issue of transformation of the judicial branch of public system in the context of the formation and development of public administration. According to various indicators, the judicial branch is a certain indicator of the development of the public administration system as a whole, on the basis of which the country’s achievement of democratic values and the level of its development as a rule of law are determined. The purpose of the article is to study the peculiarities of reforming the judicial system in the context of the formation of public administration in Ukraine. The main historical stages of the reform are identified, the peculiarities of each of them are systematized, the normative and legal principles are analyzed as prerequisites for reforming the public administration system and the judicial system, the main achievements and significance for further development are determined, and the principles for the development of the judicial system and the judiciary are outlined. The issue of administrative reforms in the context of improving public administration is also revealed. As a result of the research, four stages of the formation and reform of the judicial system of Ukraine were identified and characterized: 1991-1996 (before the adoption of the Constitution of Ukraine) - the stage of formation of the main foundations of the judicial system of Ukraine; 1996-2014, marked by the transformation of the judicial system; 2014 - 2020, the beginning of judicial reform; 2021 - and until now - development of a modern model of the judicial branch of government with the elimination of outdated forms of management and the emergence of new organizational structures in this system in wartime conditions.